Examining the Impact of Motivating and Compensating Employees on Customer Satisfaction: A Case Study of Premier Hotel, Ibadan Nigeria - Abiola-Oke, Elizabeth (My University, 2023)
This study examines the impact of motivating and compensating employees on customer satisfaction in Premier Hotel, Ibadan, Nigeria. The research focuses on the hospitality industry, particularly hotels, where customer satisfaction plays a crucial role in success. The study utilizes a case study approach, with data collected through structured questionnaires distributed to both staff and customers of Premier Hotel. Primary and secondary data sources are used, and data analysis involves descriptive and statistical methods, including Spearman’s Rank Correlation Coefficient. The findings aim to enhance understanding of the relationship between employee motivation, compensation, and customer satisfaction in the hospitality industry, providing insights for hotel management to improve practices and drive business success.